2021
DOI: 10.3389/fpls.2021.656403
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Analyses of Nutrient Control in Electrical Conductivity-Based Nutrient Recycling Soilless Culture System

Abstract: An electrical conductivity (EC)-based closed-loop soilless culture system is practical for in-field deployment. Literature on the closed-loop soilless culture nutrient management premise the limitations in managing recycled nutrients under dynamic changes in individual nutrient uptake concentrations. However, recent systems analysis studies predicting solutions for nutrient fluctuation stabilization in EC-based closed-loop soilless culture systems suggest that the system may have a deterministic side in nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
1
7
1
Order By: Relevance
“…Although several instances of under- or over-injection were observed, it is considered acceptable for management performance to remain within a 10% margin, given that practical hydroponic ion concentrations may fluctuate by more than 50% ( Ahn et al., 2021 ). Furthermore, the ion-specific nutrient management system can be improved by adopting more accurate ion sensors, pumps, and agitators for mixing the nutrient solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several instances of under- or over-injection were observed, it is considered acceptable for management performance to remain within a 10% margin, given that practical hydroponic ion concentrations may fluctuate by more than 50% ( Ahn et al., 2021 ). Furthermore, the ion-specific nutrient management system can be improved by adopting more accurate ion sensors, pumps, and agitators for mixing the nutrient solution.…”
Section: Discussionmentioning
confidence: 99%
“…However, most soilless cultivation systems replenish the nutrient solution based on the pH and electrical conductivity of the solutions, without considering the varying concentrations of individual ions ( Geoffrey et al., 1997 ; Domingues et al., 2012 ; Katsoulas et al., 2015 ; Kozai et al., 2018 ; Son et al., 2020 ). Furthermore, nutrient uptake rates vary with the growth and development of plants, adding complexity to the management of nutrient composition in recycled nutrient solutions ( Sambo et al., 2019 ; Ahn et al., 2021 ). Consequently, the ion concentrations in the nutrient solution may deviate from the optimal composition, potentially compromising the crop yield and quality.…”
Section: Introductionmentioning
confidence: 99%
“…As such, nutrient monitoring techniques have been studied for both soil and soilless culture systems. A greenhouse experiment assessed soilless culture systems in various system designs, including a closed-loop system applying electrical conductivity sensors (Ahn et al, 2021). Results indicated that succeeding nutrient ratios could be controlled by utilizing a computed nutrient ratio specifically within a closed-loop system setup.…”
Section: Models and Controlsmentioning
confidence: 99%
“…▪ The application of electrical conductivity sensors in closedloop soil and soilless growing cultures allows for the predetermination of a plant's future nutrient needs. 1 ▪ Nutrients are most commonly introduced and maintained through water within a greenhouse agriculture system.…”
Section: Growing Conditionsmentioning
confidence: 99%